SUATU KAJIAN HUKUM TERHADAP PERLINDUNGAN PEKERJA/BURUH DI KABUPATEN HALMAHERA UTARA BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Selfianus Laritmas (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The form of wage protection is the goal of the worker/laborer in doing the work to earn sufficient income to finance his life with his family, which is a decent living for humanity. During this time workers always neglected their rights in doing the work. Issues discussed in this paper are Is legal protection for workers/laborers in North Halmahera Regency in compliance with Law Number 13 Year 2003 on Manpower and What are the Barriers in Legal Protection for Workers? This research is conducted by using type of juridical Normative legal research. so the source of the Law material is analyzed is the legal material by using the Law and Case Approach. Against the results of the study "a Legal Study on the Protection of Workers/Workers in North Halmahera Regency Based on Law Number 13 Year 2003 on Manpower. Keywords: Labor Law Protection.